Factors relate to the hypercreatininemia event of patients at the risk of metabolic syndrome in Jetis I public health center - Akrom Akrom; Endang Darmawan; Nuril Maulida (Universitas Ahmad Dahlan, 2017)
Metabolic syndrome (MS) is a risk factor for chronic kidney disease (CKD). Adherence to drug therapy is one of the keys to achieving therapeutic targets in MS. Hyperuricemia (>7mg/dL in men &>5.4mg/dL in women) and hypercreatininemia (>1.3 mg/dL) is a sign of kidney function deficiency. Kidney function deficiency is the result of uncontrolled blood pressure and blood sugar levels in MS patients. The objective of the study was to know the description of the incidence of hypercreatininemia and factors related to the incidence of hypercreatininemia in outpatient at risk of MS at Jetis Public health center (PHC) I, Bantul, Yogyakarta. The analytical observational research with cross sectional design was performed on 99 MS outpatient at Jetis I Public Health Center (PHC) who fulfilled the inclusion criteria and approved the participation in the study. Blood urea and creatinine levels were determined by spectrophotometer 5010. Demographic, diagnosis and treatment data were colleccted from medical record. Patient adherence data were collected by interview. Patient compliance was measured by a medication compliance questionnaire. Demographic and clinical data are presented descriptively. Bivariate analysis with chisquare was performed to determine the value of the relationship between sex, age, hyperuricemia and adherence to the incidence of hypercreatininemia. About 30.3% of total of outpatients at risk of MS at Jetis I PHC, Bantul, is non-adherence and 69.7% is adherence to the treatment. As many as 44.4% of respondents have hypercreatininemia and 8.1% of respondents have hyperuricemia. There was a relationship between adherence and female sex with the prevalence of hypercreatininemia with an odds ratio of 3.8, 0.26 and 7.1 respectively. Based on the data of the study concluded that non-adherence, male sex and hyperuricemia are associated with the prevalence of hypercreatininemia in patients at risk of MS in Jetis I PHC.